LINC00467 Promotes Prostate Cancer Progression via M2 Macrophage Polarization and the miR-494-3p/STAT3 Axis - Jiang, Hao; Deng, Wen; Zhu, Ke; Zeng, Zhenhao; Hu, Bing; Zhou, Zhengtao; Xie, An; Zhang, Cheng; Fu, Bin; Zhou, Xiaochen; Wang, Gongxian (Frontiers in Oncology, 2021)
Background The long non-coding RNA LINC00467 plays a vital role in many malignancies. Nevertheless, the role of LINC00467 in prostate carcinoma (PC) is unknown. Herein, we aimed to explore the mechanism by which LINC00467 regulates PC progression. Methods We used bioinformatics analyses and RT-qPCR to investigate the expression of LINC00467 in PC tissues and cells. The function of LINC00467 in the progression of PC was confirmed by loss-of-function experiments. PC cell proliferation was assessed by CCK-8 and EdU assays. The cell cycle progression of PC cells was examined by flow cytometry. Moreover, Transwell assays were used to investigate the migration and invasion of PC cells. Western blot assays were used to detect the expression of factors associated with epithelial–mesenchymal transition. The interactions of LINC00467 with prostate cancer progression and M2 macrophage polarization were confirmed by RT-qPCR. The subcellular localization of LINC00467 was investigated via the fractionation of nuclear and cytoplasmic RNA. Bioinformatics data analysis was used to predict the correlation of LINC00467 expression with miR-494-3p expression. LINC00467/miR-494-3p/STAT3 interactions were identified by using a dual-luciferase reporter system. Finally, the influence of LINC00467 expression on PC progression was investigated with an in vivo nude mouse model of tumorigenesis. Results We established that LINC00467 expression was upregulated in PC tissues and cells. Downregulated LINC00467 expression inhibited PC cell growth, cell cycle progression, migration, and invasion. Downregulated LINC00467 expression similarly inhibited PC cell migration via M2 macrophage polarization. Western blot analysis showed that LINC00467 could regulate the STAT3 pathway. We established that LINC00467 is mainly localized to the cytoplasm. Bioinformatics analysis and rescue experiments indicated that LINC00467 promotes PC progression via the miR-494-3p/STAT3 axis. Downregulated LINC00467 expression was also able to suppress PC tumor growth in vivo. Conclusions Our study reveals that LINC00467 promotes prostate cancer progression via M2 macrophage polarization and the miR-494-3p/STAT3 axis.